Controlling the Cost of Reliability in Peer-to-peer Overlays - Mahajan, Ratul; Castro, Miguel; Rowstron, Ant (IPTPS'03, 2003)
Structured peer-to-peer overlay networks provide a useful substrate for building distributed applications but there are general concerns over the cost of maintaining these overlays. The current approach is to configure the overlays statically and conservatively to achieve the desired reliability even under uncommon adverse conditions. This results in high cost in the common case, or poor reliability in worse than expected conditions. We analyze the cost of overlay maintenance in realistic dynamic environments and design novel techniques to reduce this cost by adapting to the operating conditions. With our techniques, the concerns over the overlay maintenance cost are no longer warranted. Simulations using real traces show that they enable high reliability and performance even in very adverse conditions with low maintenance cost.